KONTRIBUSI REMITAN TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI KABUPATEN WONOGIRI - BAROKAH, UMI (Universitas Sebelas Maret, 2009)
This research aims to understanding the amount of remittance and its contribution toward the income farm households at Wonogiri regency. The result analysis shows that remittance up to Rp. 1.331.984 or 12,43% total income farm household.